2021
DOI: 10.1128/jvi.02446-20
|View full text |Cite
|
Sign up to set email alerts
|

A Persistent Giant Algal Virus, with a Unique Morphology, Encodes an Unprecedented Number of Genes Involved in Energy Metabolism

Abstract: Viruses have long been viewed as entities possessing extremely limited metabolic capacities. Over the last decade, however, this view has been challenged, as metabolic genes have been identified in viruses possessing large genomes and virions—the synthesis of which is energetically demanding. Here, we unveil peculiar phenotypic and genomic features of Prymnesium kappa virus RF01 (PkV RF01), a giant virus of the Mimiviridae family. We found that this virus encodes an unprecedented number of proteins involved in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 109 publications
3
39
0
Order By: Relevance
“…Conversely, our results suggested that retaining structural zeros did not negatively influence the result, which indicates that the “presence-absence” pattern is as informative as the “more-less” pattern when identifying NCLDV-host relationships. This result is consistent with a previous “K-r-strategist” hypothesis: some NCLDVs, like mimiviruses, are K-strategists that decay slowly and can form stable associations with their hosts ( 52 , 53 ). A recent report supported these non-“boom and bust” dynamics of prasinoviruses and their hosts with an experiment-based mathematical model ( 54 ).…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, our results suggested that retaining structural zeros did not negatively influence the result, which indicates that the “presence-absence” pattern is as informative as the “more-less” pattern when identifying NCLDV-host relationships. This result is consistent with a previous “K-r-strategist” hypothesis: some NCLDVs, like mimiviruses, are K-strategists that decay slowly and can form stable associations with their hosts ( 52 , 53 ). A recent report supported these non-“boom and bust” dynamics of prasinoviruses and their hosts with an experiment-based mathematical model ( 54 ).…”
Section: Discussionsupporting
confidence: 92%
“…These genes, often called auxiliary metabolic genes, are considered to function in reprogramming host metabolism and molecular machinery during viral infection toward enhancing viral replication and subsequent transmission to another host. For example, the recently characterized Prymnesium kappa virus RF01 encodes genes for all four succinate dehydrogenase subunits, as well as genes for modulating β-oxidation pathway ( Blanc-Mathieu et al, 2021 ). These viral genes are suggested to boost energy production during viral replication, which can deteriorate host metabolism, or to enhance the supply of building blocks for viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…These genes make the viruses more independent from their hosts by allowing the virus to manipulate the host during infection. The functions of AMGs have been linked to central roles in photosynthesis in cyanobacteria (Lindell et al ., 2004), sphingolipid biosynthesis of E. huxleyi (Moniruzzaman et al ., 2020; Schulz et al ., 2020), nitrogen uptake in Ostreococcus (Monier et al ., 2017) and even central roles in the tricarboxylic acid (TCA) cycle/oxidative phosphorylation chain, potentially controlling energy production in the host cells during infections (Blanc‐Mathieu et al ., 2021).…”
Section: Marine Haptophytes and Their Dsdna Virusesmentioning
confidence: 99%